Mitochondrial dynamics in vascular remodeling and target-organ damage - Zhu, Tong; Hu, Qingxun; Yuan, Yanggang; Yao, Huijuan; Zhang, Jian; Qi, Jia (Frontiers in Cardiovascular Medicine, 2023)
Vascular remodeling is the pathological basis for the development of many cardiovascular diseases. The mechanisms underlying endothelial cell dysfunction, smooth muscle cell phenotypic switching, fibroblast activation and inflammatory macrophage differentiation during vascular remodeling remain elusive. Mitochondria are highly dynamic organelles. Recent studies showed that mitochondrial fusion and fission play crucial roles in vascular remodeling and that the delicate balance of fusion-fission may be more important than individual processes. In addition, vascular remodeling may also lead to target-organ damage by interfering with the blood supply to major body organs such as the heart, brain and kidney. The protective effect of mitochondrial dynamics modulators on target-organs has been demonstrated in numerous studies, but whether they can be used for the treatment of related cardiovascular diseases needs to be verified in future clinical studies. Herein, we summarize recent advances regarding mitochondrial dynamics in multiple cells involved in vascular remodeling and associated target-organ damage.